The Designs of Case Method Based and Project Based Learnings in Indonesian Literature Course - Muhammad Joharis; Atika Wasilah; Tasya Aulia Rahmah; Mega Rebeca Gita (BIRCU, 2022)
This study aims to design case-based learning and project-based learning in Indonesian language literature course that can help teaching and learning activities so that the study can be learned independently, understandable, reasonable and communicative effectively as well as can solve problems in various contexts in everyday life. The method used in this study is library research, which collects any data from a study of books, journal literature, notes and reports related to the problems studied, that is designs of case method based and project base learnings in Indonesian literature course. The design of case method-based learning and project-based learning are critical thinking, problem solving, and collaboration.